Short communication. Isolation of Aeromonas hydrophila in piglets - Queiroga, M. C.; Amaral, A. S. P.; Branco, S. M. (SPANISH JOURNAL OF AGRICULTURAL RESEARCH, 2012)
The production of Alentejano breed pig started a recovery two decades ago due to increasing demand for gourmet products. These pigs are raised in rotational semi-extensive or extensive outdoor production systems in the ``Montado{''} (green and cork oak forest), grazing and feeding acorns and other associated food resources. Bacteria of the genus Aeromonas are considered as emerging pathogens of importance for man and,animals, but its involvement in swine is not well documented. In the context of a study made at the University of Evora to assess the specific diseases of Alentejano swine, diseased piglets from two farms were submitted for pathological and bacteriological examinations. Pathological examinations revealed changes characteristic of septicemia, and Aeromonas hydrophila was isolated in pure culture from multiple organs of piglets from both farms. Antibiotic sensitivity tests showed that the isolates from one of the farms were susceptible to gentamicin, oxitetracycline, neomycin, enrofloxacin, colistin sulfate, trimethoprim, ceftiofur, and amoxicillin plus clavulanic acid. In contrast, the A. hydrophila isolated in the other farm was resistant to all drugs tested but enrofloxacin. This is the first report in the world showing the relationship between septicemia and A. hydrophila infection in piglets. The importance of this finding is further reinforced by the fact that these bacteria can be highly resistant to antimicrobial agents.
The following values have no corresponding Zotero field: pub-location: AUTOPISTA A-6, KM 7 5, MADRID, 28040, SPAIN publisher: SPANISH NATL INST AGRICULTURAL & FOOD RESEARCH & TECHNOLO
Keywords: Alentejano swine breed; emerging pathogens; Iberian swine; resistance to antibiotics